PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI PADA KONSEP HYDROSFER DI KELAS X5 SMA NEGERI 2 SIAKHULU (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2018)
This research is conducted in order to find out students’ result on geography subject in X.5 class of SMA Negeri 2 Siakhulu academic year 2015/2016, after applying Cooperative Learning Model of Number Head Together (NHT). The subject of the research is X.5 students of SMA Negeri 2 Siakhulu. The CAR is conducted in two cycles. The data analysis is done by doing test, interview, observation and documentation. Technique for data analysis used is interactive model analysis, which consist of data reduction, data presentation and conclusion. Based on the research done, it can be concluded that by applying Cooperative Learning Model of Number Head Together (NHT), it can improve students’ learning result on Hydrosfer Concept in X.5 of SMA Negeri 2 Siakhulu academic year 2015/2016. This can be seen from the improvement of percentage of number of students who can pass above the minimum standard test result, in which only 8.6 % at the beginning, then it becomes 72 % in the first cycle, and reach 92 % in the second cycle. The average test result at the beginning is 58, then it becomes 71 in the first cycle, and 87 in the second cycle.